Identification of opportunities from FCCBs for Kotak Mahindra Asset Reconstruction Department (ARD) - Jalan, Vivek (2008)
Foreign Currency Convertible Debentures (FCCBs) have, in last 4 years, become a major and a cheaper source of finance for Indian companies. Till very recently FCCBs acquired accolades of being a flexible instrument, giving the holder the right to convert the bonds into equity and providing funds to the issuing company at negligible rate of interest. However, the sub-prime crisis in US led the financial institutional investors (FIIs) to pull-out from Indian Markets causing the Stock Market crash in India. This has resulted in a huge possibility of non-conversion of FCCBs and thus, the redemption pressure on Indian Companies. The paper deals with the opportunities arising for Kotak Asset Reconstruction Department (ARD) from such a situation.